Diagnostics of the pre-fault situation of the bolted current-carrying joint in the conditions of changing regime parameters - Kryvonosov, Valerii (Technology audit and production reserves, 2018)
The object of research is the methods of non-destructive monitoring of the state of a bolted current-carrying joint under conditions of dynamically changing current load conditions and ambient temperature. One of the most problematic places in the modern conditions of economic development of enterprises is the reduction in the accident rate of production due to the weakening of the bolted current-carrying joint. Studies of the causes of stopping electrical equipment at a number of ferrous metallurgy enterprises, mining and processing complexes, in medical institutions have shown that in 1.5-2 % of cases the cause of an emergency shutdown of electrical equipment is the weakening of the bolted current-carrying joint. The main problem of the bolted current-carrying joint is the mechanical weakening of the contact density. The appearance of a temperature gradient in the place of a bolted joint is influenced by climatic parameters and dynamically changing modes of operating current loads and network voltage. The study of operating parameters of the network and load currents is based on the use of a technique for monitoring the quality of electricity indicators using self-recording spectrum analyzers. In this study, the spectrum analyzer Fluk 435 (Ukraine) is used, the characteristics of which correspond to the ISO 9001 measurement system certificate. Statistical processing methods are used as the basis for processing the experimentally obtained data. In the course of the study, the inequality between the measured temperature of the bolted current-carrying joint and the calculated temperature of the serviceable joint is determined. The inequality is fulfilled in the sections, the stationarity of which is determined for deterministic and random modes of change of the controlled parameters. The functions of Boolean variables are compiled, the disjunctive functions that determine the normal and pre-crash modes of the bolted joint are minimized. The obtained theoretical results allow developing algorithms and devices for diagnosing and protecting equipment. This provides the opportunity to reduce the accident rate of the equipment. Compared with similar well-known protection equipment, taking into account the modes of load currents, mains voltage and ambient temperature provides a high sensitivity and accuracy of detecting the initial moment of loosening of a bolted current-carrying joint.